Teacher Solutions for Dealing with Student Character inImplementing Differentiated Learning at SMA Negeri 3 Tanjung Pinang - Oktavia, Putri Nada; Hawa, Isma; Delpita, Sri; Putri, Riri Indriana; Fatmila, Dewi; Nevrita, Nevrita (DIDAKTIKA, 2024)
This research aims to find out teacher solutions in dealing with student character in implementing differentiated learning at SMA Negeri 3 Tanjungpinang. This research is a qualitative descriptive study with primary and secondary data sources. The methods used are observation, interviews, and documentation as well as literature reviews to collect data available from various sources. The results of this research are that differentiated learning will provide greater freedom for students to develop their internal skills or abilities. Apart from that, differentiated learning can improve student learning achievement, increase student motivation and interest in learning and can increase student involvement in the learning process in the classroom. The conclusion of this research is that in implementing differentiated learning teachers must be able to plan learning according to student characteristics. Apart from that, teachers must also be able to apply various methods, media and learning resources.